The Summer Of The Swans - Byars, Betsy; CoConis, Ted (New York Viking Penguin, 1970)
A teen-age girl gains new insight into herself and her family when her mentally retarded brother gets lost
American Corner
Awarded The John Newbery Medal
11
Keywords: English Fiction; English Stories